Examining the interaction between artificial intelligence literacy and individual entrepreneurial orientation in teacher candidates: The mediating role of sustainable development - Polat, Ebru; Zincirli, Muhammed; Zengin, Erdal (Elsevier Sci Ltd, 2025)
This study investigates the effect of artificial intelligence literacy on individual entrepreneurial orientation through sustainable development behaviors using structural equation modeling. Conducted with pre-service teachers, the research utilized artificial intelligence literacy, sustainable development behavior, and individual entrepreneurship orientation scales. Data analysis involved structural equation modeling and bootstrap methods. Results indicated that artificial intelligence literacy positively influenced both sustainable development behaviors and individual entrepreneurial orientation. A moderate positive correlation was found between artificial intelligence literacy and sustainable development behaviors (r = 0.41, p < .01) and individual entrepreneurship orientation (r = 0.39, p < .01). Additionally, sustainable development behaviors had a significant effect on individual entrepreneurial orientation (beta = 0.426, p < .000). The structural equation model exhibited good fit indices, and the total effect of artificial intelligence literacy on individual entrepreneurial orientation was positive and significant (beta = 0.433, p < .000). Together, artificial intelligence literacy and sustainable development behaviors explained 33% of individual entrepreneurial orientation. This study introduced a specific pedagogical innovation by integrating artificial intelligence literacy into teacher training, which aimed to develop critical skills essential for entrepreneurial orientation and sustainable development. By emphasizing the mediating role of sustainable development behaviors, the study highlighted its contribution to advancing responsible management and sustainability in education.
Keywords: Artificial intelligence literacy; Individual entrepreneurial orientation; Sustainable development